ショウワキチ ニオケ ルニッショク カンソク ケッカ - 長谷川, 貞雄; ハセガワ, サダオ; 川尻, 矗大; カワジリ, ノブヒロ; HASEGAWA, Sadao; KAWAJIRI, Nobuhiro (国立極地研究所, 1964)
P(論文) 1961年8月11日,昭和基地北方洋上に生じた金環食の際,基地において電離層観測を実施したので,その結果を報告する.この日食時には太陽高度が非常に低く,しかも若干電離層擾乱を伴っていたために,電離層の下部領域即ちE層,F_1層は観測し得なかったが,F_2領域については明らかに日食の影響が認められた.この領域について得られた主な結果を次に示す.1.F_2領域の電子消滅は主に付着作用によって行なわれ,その付着係数Bは高度300km付近において,1.5～2.0×10^<-4>sec^<-1>の値が得られた.2.この付着係数Bの値を用いて求めた理論計算曲線は,食甚時まで観測値とよく一致するが,復円時には異常な電子密度増加が認められて,理論曲線とは一致しなかった.この原因として,荷電微粒子群の進入による電離を考え,日食期間のその電子生成率q'を求めると,平均70cm^<-3>sec^<-1>の値が得られた.3.付着係数Bの値を各高度に対して求め,それによりscale heightを求めた結果,高度300km付近におけるF_2領域においては,酸素分子0_2に対する電子付着作用を仮定して,約30kmであった. During the solar eclipse on August 11, 1961, the continuous recording of h'-f observation was made in vertical incidence at Syowa Base in Antarctica, and in spite of the period of very low solar zenith angle, it was possible to find the effect of the eclipse on the ionograms. The recordings at this time were obtained of only the F2 region in the ionosphere, and the variation of electron density during the solar eclipse at a certain height of the F2 region was more remarkable than the variation of the critical frequency. The results of analysis of the observations are summarized as follows: (i) Electron in the F2 region seems to decrease by the attachment process, and the order of magnitude of the attachment coefficient can be estimated at 1.5×10^<-4> to 2.0×10^<-4>sec^<-1> at 300km. (ii) On the assumption of the above-mentioned values as the attachment coefficient, the computed values of an electron density during the eclipse show a good agreement with the observational values up to the maximum phase of the eclipse, but beyond the maximum phase, the observational values continue to increase rapidly in electron density until after the end of eclipse. It may be suggested that the phenomena of electron increase are due to an effect such as the ionization of charged particles, (iii) In our observation, the value of scale height obtained, as the attachment process of electron to (O_2) oxygen, is about 30 km at 300 km levels of the F2 layer. departmental bulletin paper